Simulating grain yield of irrigated rice in climate change scenarios - Walter, Lidiane Cristine; Rosa, Hamilton Telles; Streck, Nereu Augusto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to simulate rice grain yield in climate change scenarios with increasing of current atmospheric CO2 concentration and increases in mean air temperature in Santa Maria, RS, as well as to verify possible implications on current recommendations of sowing period. Climate change scenarios for the next one hundred years considering doubled CO2 concentration and increases of 1, 2, 3, 4 and 5°C were used. Rice grain yield was simulated with the InfoCrop model. Simulations were performed considering three rice cultivars – IRGA 421, IRGA 417 and EPAGRI 109 – and seven sowing dates spaced monthly from July 20th to January 20th. An increase in rice grain yield was observed in the climate change scenarios simulated for the three cultivars, with higher increase for the very early cultivar (IRGA 421) and lower increase for the late cultivar (EPAGRI 109). If climate change takes place, currently sowing period recommended for irrigated rice shall be enlarged.